Faktor-Faktor yang Mempengaruhi Kecemasan Mahasiswa dalam Menghadapi Tugas Akhir - Ramadhan Trybahari Sugiharno; Wibowo Hanafi Ari Susanto; Frengki Wospakrik (Jurnal Keperawatan Silampari, 2022)
This study aims to look at the factors that influence students in facing their final project. This research method is quantitative research with a cross-sectional study design. The results showed that the average age of the respondents was 21 years, with the youngest 20 years old and the oldest 22 years old. Most (76.3%) of the research respondents were 45, and of the total respondents, the majority (64.9%) of 24 respondents experienced moderate anxiety. And 31 respondents (83.8%) have high family support then, strong peer influence is 31 respondents (83.8%), the influence of supervisors is vital to as many as 33 respondents (89.2%), and the influence of the environment good as many as 30 respondents (81.1%). The bivariate analysis results showed that the p-values ​​for all variables were < 0.05. In conclusion, there is a significant relationship between support from family, peers, supervisors, and the environment with student anxiety in facing the final project. Keywords: Student, Anxiety, Nursing, Final Project